Examining the clinical validity of the global psychotrauma screen in refugees - Pinto, Janaina V.; Hoeboer, Christopher; Hunt, Caroline; O’Toole, Brian; Olff, Miranda (Frontiers in Psychology, 2024)
Introduction The Global Psychotrauma Screen (GPS) is a brief transdiagnostic screener that covers a broad range of trauma-related disorders as well as risk factors known to influence the course of symptoms. Methods We analyzed data from African war refugees in Australia (n = 70), including the GPS, the Structured Clinical Interview for DSM-5 Disorders (SCID-5), the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), and the Brief Resilience Scale (BRS). Results Using the Youden’s J Index to examine the clinical validity of the GPS subscales measuring PTSD, dissociation, depression, and generalized anxiety disorder (GAD), we found that a PTSD subscale score of 3 or higher, and a depression and dissociation subscale score of 1 or higher, was optimally efficient for detecting a probable diagnosis (Youden’s J = 0.76, J = 0.72, and J = 0.90, respectively) with high sensitivity and specificity. We were unable to test the GPS clinical validity for GAD due to the low GAD occurrence. The GPS resilience item was not related to the total score (r = 0.02), indicating low convergent validity for resilience. Risk factors, including current stressors and childhood trauma history, were related to more severe GPS symptom scores, while lack of resilience, social support, and history of mental illness were not. Conclusion We conclude that the GPS may be a useful screening tool for PTSD, depression, and the dissociative subtype in refugees.